Pelatihan Canva Untuk Penguatan Identitas Visual dan Promosi PPDB PAUD - Nurfaizah; Wisnu Muamar; Iwan Haryanto; Didit Suhartono; Muliasari Pinilih (CV. Multi Kreasi Media, 2026)
Limited visual design capacity in community-based early childhood education institutions can constrain public communication and new student admission promotion. Prior to the program, the partner institutions mainly disseminated school information through plain text messages and had not established consistent visual materials. This community service program aimed to strengthen teachers' ability to produce Canva-based visual communication materials while establishing reusable institutional templates. The training was conducted on 9 May 2026 at KB Tunas Bangsa, Kediri Village, Karanglewas District, Banyumas Regency, involving six teachers from KB Tunas Bangsa and TK Pertiwi 5 Kediri. A product-based training approach was implemented through three stages: introduction to Canva and basic visual design principles, guided design practice, and template standardization with distribution preparation. Achievement was evaluated descriptively based on product completion. All participants completed a school introduction poster and a new student admission flyer that were ready for print and digital distribution. A reusable institutional template was also established to support continuity of visual communication. The activity indicates that Canva is a feasible tool for resource-constrained early childhood education institutions to improve consistency in public-facing visual communication. Nevertheless, the program did not employ pre-test/post-test measures or assess the impact of the materials on communication reach and enrolment outcomes; therefore, follow-up evaluation is required.